(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
This text is the unpublished translation of a fragment of the article co-written by the project manager of the Portail des Arts de la Marionnette (https://lelab.artsdelamarionnette.eu) and by the innovation director of the service provider PMB Services. The original text (in French) was published in two parts, one in 2021 and the other in 2022, in Les Cahiers de la Documentation (ABD/BVD, Brussels). The text presents the experience of this online valuation project of a set of heterogeneous data (library catalogues, digitized objects and documents and related metadata, research data) produced by a consortium currently composed of twenty-seven institutions and coordinated since 2009 by the Institut International de la Marionnette-IIM (France). This valuation is carried out through the PMB free software, on a semantic model notably inspired by FRBRoo and SKOS.